Organizational support and task performance: a multiple mediation model - Chu, Xiaoyuan; Yu, Jingyue; Litifu, Alafate; Zhao, Wenlu; Wei, Xinyi; Wang, Pengcheng; Wei, Jun (Frontiers in Psychology, 2024)
Objective Organizational support has been identified as one of the causes for task performance, while previous studies have not adequately explored the underlying mechanisms. Thus, this study aims to reveal the potential mechanisms that linked organizational support to task performance. Methods A questionnaire survey was conducted among the 720 participants from 12 audit firms in Beijing in December 2020. Participants completed anonymous questionnaires assessing their organizational support, task performance, organizational commitment, and job satisfaction. Data analysis was conducted with SPSS 26.0. Results (1) Organizational support was positively associated with task performance, (2) job satisfaction and organizational commitment both mediated the relationship between organizational support and task performance respectively, and (3) the relationship between organizational support and task performance was also serially mediated by job satisfaction and then organizational commitment. Conclusion Job satisfaction and organizational commitment played a serial multiple mediating role in the association between organizational support and task performance, which provides a potential path for improving task performance.